IMPROVING KNOWLEDGE OF ONLINE MOTORCYCLE TAXI DRIVERS (OJOL) ABOUT EMERGENCY MANAGEMENT OF FRACTURES WITH SPLINTS ON THE ROAD - Sahuri Teguh Kurniawan; Saelan Saelan; Galih Setia Adi (Journal of Health Community Service, 2021)
The incidence of fractures is the highest prevalence in the world. Fractures by accidents require serious management to prevent serious injuries. The improper first treatment of fracture victims can lead to death and disability. The causes of fractures in Indonesia include traffic accidents. The number of motorized vehicles in Indonesia is increasing by 119.560 cases every year which caused new problems, including security, safety, and traffic congestion. Online motorcycle taxis are alternative public transportation because they can reach places that are not passed by other public transportation. Online motorcycle taxis riders are people who are often on the road and often see even as victims of broken bones from traffic accidents, so there is a need for counseling and handling emergency conditions for motorcycle taxi drivers on the road. This community service activity aimed to increase the ojol drivers’ knowledge and ability in dealing with emergency fractures on the road using discussion methods. The activity was carried out on Thursday, July 16, 2020, carried out face-to-face in the Sukoharjo Regency pavilion, followed by a number of 20 participants. The result of this activity found an increase in the knowledge of ojol drivers by 40% with posttest results of 80% continued with splint dressing. The results of these activities were followed up by coordination with Gojek for greater community service.